Origin and Age of Magmatism in the Northern Philippine Sea Basins - Osamu Ishizuka; Kenichiro Tani; Rex N. Taylor; Susumu Umino; Izumi Sakamoto; Yuka Yokoyama; Gen Shimoda; Yumiko Harigane; Yasuhiko Ohara; Chris E. Conway; Americus Perez; Shun Sekimoto (Geochemistry, Geophysics, Geosystems, 2022)
Abstract A Robust tectonic reconstruction of the Philippine Sea Plate around ∼52 Ma is a prerequisite in understanding the process of subduction initiation and establishment of the Izu‐Bonin‐Mariana arc. This study investigates origins and timing of basin formation in the still poorly understood oldest part of the northern Philippine Sea plate. We have established that andesitic magmatism in the form of the Northern Philippine Sea volcanics is widely distributed across this area. It is founded on both a Mesozoic arc terrane (Daito Ridge Group) and an intervening basin (Kita‐Daito Basin). Their narrow Eocene age range (45‐41 Ma) and lack of systematic spatial variation in geochemistry implies that this magmatism was not associated with on‐going subduction, but related to the rifting/spreading event forming the Kita‐Daito Basin. The arc‐like geochemistry of the volcanics seems to indicate melting of lithospheric mantle which had been previously metasomatized by Mesozoic subduction of a plate with Pacific‐MORB isotopic characteristics. Late Eocene basaltic magmatism also found in the Kita‐Daito Basin does not have arc‐like characteristics, and could have formed from low‐degree melts of asthenospheric mantle associated with the final stage of Kita‐Daito Basin spreading. As onset of activity of the Northern Philippine Sea volcanics is essentially synchronous with the magmatism associated with the Oki‐Daito mantle plume, it is possible that both magmatism and rifting of the Kita‐Daito Basin were triggered by the arrival of the Oki‐Daito mantle plume in this region. These results demonstrate that the Kita‐Daito Basin postdates subduction initiation of the Pacific Plate along the Izu‐Bonin‐Mariana arc.